О новом диагностическом признаке клещей рода Dendrolaelaps Нalbert, 1915 - Щербак, Г.И. (Вестник зоологии, 1973)
A description and drawings are given of a pipe-like organ found in females of 12 species of mites from the genus Dendrolaelaps. The organ is located inside the first —third joints of legs III and possess a shape typical of each species. Absence of this organ in all immature individuals and in males testifies to the fact that it is a part of the female reproductive system. An assumption is advanced that the described organ is a spermatheca and canals connected with it.